2019
DOI: 10.1101/2019.12.20.885400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dihydroartemisinin-loaded Magnetic Nanoparticles for Enhanced Chemodynamic Therapy

Abstract: 13Recently, chemodynamic therapy (CDT) has represented a new approach for cancer treatment with 14 low toxicity and side effects. Nonetheless, it has been a challenge to improve the therapeutic effect 15 through increasing the amount of reactive oxygen species (ROS). Herein, we increased the amount of 16ROS agents in the Fenton-like reaction by loading dihydroartemisinin (DHA) which was an artemisinin 17 (ART) derivative containing peroxide groups, into magnetic nanoparticles (MNP), thereby improving 18 the th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The cases above have revealed that targeting to the acidic endo/lysosome is a promising way to achieve Fe 2+ /Fe 3+ release from iron oxide nanoparticles. By following these studies, several ARTs nanosystems have been reported most recently (Wang D. et al, 2017;Zhang et al, 2017;Pan et al, 2018;Guo et al, 2019;Li et al, 2019;Qin et al, 2019). Generally, nanoparticles are easy to be chemically modified with additional ligands to strengthen the functionalities.…”
Section: Arts Nanotherapeutics Iron Oxide-based Arts Nanotherapeuticsmentioning
confidence: 99%
“…The cases above have revealed that targeting to the acidic endo/lysosome is a promising way to achieve Fe 2+ /Fe 3+ release from iron oxide nanoparticles. By following these studies, several ARTs nanosystems have been reported most recently (Wang D. et al, 2017;Zhang et al, 2017;Pan et al, 2018;Guo et al, 2019;Li et al, 2019;Qin et al, 2019). Generally, nanoparticles are easy to be chemically modified with additional ligands to strengthen the functionalities.…”
Section: Arts Nanotherapeutics Iron Oxide-based Arts Nanotherapeuticsmentioning
confidence: 99%